Factors Affecting Innovation Adoption Crop-Livestock Integration System (SITT) in North Minahasa Regency - Tumewu, Judy Mathilda; Warouw, Zadrak M.; Endoh, Eusebius K. M. (International Journal of Applied Business and International Management, 2024)
The adoption of beef cattle crop-livestock integration system (SITT) innovations in North Minahasa district still faces various obstacles. As a result, beef cattle development tends to experience a decline in population, productivity and competitiveness. This is due to the low application of technology. The solution to overcome this problem is to apply the Livestock Crop Integration System (SITT) pattern.  The purpose of the study was to determine the factors influencing farmers' attitudes and adoption of SITT technology innovations for beef cattle in North Minahasa district. Descriptive research was conducted from March to May 2024, where 25 extension agents and cattle farmers were selected purposively.  The variables used were farmer characteristics, extension worker performance, nature of innovation, communication channels, attitudes and farmer adoption of SITT. Data analysis used the Spearman rank method, to show whether there is a significant relationship between each variable. The results of the study stated that there was a strong relationship between the dimensions of extension (extension performance, nature of innovation) with the dimensions of farmer attitudes and adoption dimensions, while communication behavior (extension dimensions) with the dimensions of farmer attitudes and adoption, had a weak relationship.  In conclusion, In partial terms, the dimensions of extension workers' performance and the nature of innovation have a significant effect on the attitude of beef cattle farmers and the adoption of SITT technology in North Minahasa district, while the dimensions of extension workers' communication behavior have no significant effect. Simultaneously, the dimensions of extension agents consisting of extension agent performance, innovation traits and communication behavior have a significant effect on the attitude of beef cattle farmers and the adoption of SITT technology in North Minahasa district. The attitude dimension of beef cattle farmers significantly influences the adoption dimension of SITT technology in North Minahasa district